Net load forecasting in presence of renewable power curtailment - Fonte, Pedro M (2016)
This paper analyzes a real case study based on na islanding power grid, where there is wind power curtailment during the grid operation. This curtailment skews the wind power production database creating a huge challenge to the overall power production forecast. Thus, it is presented a solution which has allowed more accurate forecasts in order to improve the renewable production and reduce the fuel consumption in thermal power plants. The proposed filtering approach demonstrated to be a good solution allowing wind power forecasts with less error and net load forecasts with more accuracy.